CURRENT DESIGN TRENDS IN COMPUTER GAME ADVERTISING - HOVHANNISYAN, S. V.; HULA , Y. P.; MAZNICHENKO, O. V.; BOLDYREVA, O. A. (Art and Design, 2022)
The purpose of the study is to analyze and identify the main trends in computer game advertising and its design. Research of functional and visual features of the design of certain types of Internet advertising. Methodology. The research methodology is based on a systematic analysis of scientific works mainly thematically related to Internet advertising and the features of its design for different platforms. Visual analytical, comparative, and monographic methods of scientific analysis of sources are used in this paper. Results. The current trends in advertising, which are most relevant for the gaming industry today, were studied. Therefore greater emphasis has been placed on the three most popular and relevant to the game field types of online advertising and their graphic design features. Based on the analysis of scientific works and responses from people on Internet sites, a significant interest in Internet advertising was found in contrast to traditional form of advertising, namely the banner, video advertising and blogging. The features, advantages, and disadvantages of each of these types of online advertising have been identified. It has been clarified which aspects in the design of these types of advertising are important. The reasons for the success of the use of these types of online advertising in the field of games and their psychological impact on the consumer are analyzed. The importance of the right approach to the design of these types of advertising is determined. Scientific novelty of the research lies in summarizing previous research on this topic and identifying the features of certain types of online advertising, structuring information about the advantages and disadvantages of each, identifying the design features of each type, as well as analyzing the reasons for their success in gaming and the role of graphic design in this. Practical significance. Research materials can be used as a theoretical basis for the creation of projects related to computer games advertising. Researched information and scientific materials of various authors allowed us to create an informative article, the content of which can be useful in developing appropriate design projects and choosing the direction of advertising for them.